Performance Assessment of Eco-Friendly Asphalt Binders Using Natural Asphalt and Waste Engine Oil - Albayati, Amjad H.; Al-Kheetan, Mazen J.; Mohammed, Ahmed M.; Al-ani, Aliaa F.; Moudhafar, Mustafa M. (Infrastructures (Basel), 2024)
The depletion of petroleum reserves and increasing environmental concerns have driven the development of eco-friendly asphalt binders. This research investigates the performance of natural asphalt (NA) modified with waste engine oil (WEO) as a sustainable alternative to conventional petroleum asphalt (PA). The study examines NA modified with 10%, 20%, and 30% WEO by the weight of asphalt to identify an optimal blend ratio that enhances the binder’s flexibility and workability while maintaining high-temperature stability. Comprehensive testing was conducted, including penetration, softening point, viscosity, ductility, multiple stress creep recovery (MSCR), linear amplitude sweep (LAS), energy-dispersive X-ray spectroscopy (EDX), Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscopy (SEM). The results reveal that WEO effectively softens NA, improves ductility, and enhances workability, with the 20% WEO blend achieving the best balance of physical and rheological properties. Chemical analysis indicates that WEO increases carbon content and reduces sulfur and impurities, aligning NA’s composition closer to PA. However, excessive WEO (30%) compromises thermal stability and deformation resistance. The findings underscore the potential of WEO-modified NA for sustainable pavement applications, with 20% WEO identified as the optimal content to achieve performance comparable to conventional petroleum asphalt while promoting environmental sustainability.